Integration of Project-Based Learning and STEM for Climate Change Education toward the UN SDGs - Hana Lestari; Tri Suryaningsih; Gendis Seruni (JENIUS (Journal of Education Policy and Elementary Education Issues), 2026)
Climate change education requires learning approaches that not only enhance conceptual understanding but also develop climate literacy in an integrated manner. This study aimed to investigate the effects of STEM-integrated Project-Based Learning (PjBL–STEM) on ecological concept mastery and climate literacy among prospective elementary school teachers. In this study, climate literacy was operationalised as students’ ability to understand climate change concepts, analyse climate-related information, evaluate environmental impacts, and formulate mitigation and adaptation strategies. A quasi-experimental pretest–posttest control group design was employed involving 72 students enrolled in an Environmental Education course, consisting of an experimental group (n = 36) and a control group (n = 36). Data were collected using validated essay-based assessments and analysed using N-gain, independent-samples t-tests, and Multivariate Analysis of Variance (MANOVA). The results showed that the PjBL–STEM group achieved higher learning gains in ecological concept mastery (N-gain = 0.35, moderate) and climate literacy (N-gain = 0.42, moderate) than the control group. Independent-samples t-tests revealed significant differences between groups for both variables (p < .05). Furthermore, MANOVA revealed a significant multivariate effect of the learning model on the combined dependent variables, Wilks’ Λ = 0.688, F(2,69) = 15.42, p < .001, partial η² = .312, indicating a substantial effect of PjBL–STEM on ecological concept mastery and climate literacy simultaneously. These findings suggest that PjBL–STEM provides an effective framework for promoting ecological understanding and climate literacy through authentic, inquiry-based, and interdisciplinary learning experiences. Therefore, PjBL–STEM has the potential to support climate change education and contribute to the achievement of SDG 4 (Quality Education) and SDG 13 (Climate Action).